The strategy workout : the 10 tried-and-tested steps that will build your strategic thinking skills - Ross, Bernard, 1953-; Segal, Clare, 1957- (Business gym, 2016)
The Strategy Workout has been specially developed to be clear, simple, very easy to follow and highly effective. Our unique pre-workout test will help you identify your weak and strong points and the straightforward 10-step improvement plan will show you how you can quickly boost your skills.